Local Genius Mabbelle: Analysis of Increasing Students' Metacognition Skills Through Augmented Reality-Based Educational Learning Media - Dewi, Sartika Sari; Asfar, Andi Muhammad Irfan Taufan; Asfar, Andi Muhamad Iqbal Akbar; Muhlis, Muhlis; Nurannisa, Andi (UNIMUS Web Conferences, 2025)
Metacognitive skills is an essential component of Higher Order Thinking Skills (HOTS), are critical in equipping students to solve complex, context-based problems. A 2022 survey by the McKinsey Global Institute identifies metacognitive skills as a primary predictor of students' performance, particularly in adapting to the changes posed by the era of Society 5.0. Despite this importance, metacognitive skills among students in Indonesia remain low, many students struggle to comprehend material and complete tasks requiring high-level thinking. This study, conducted at UPT SMP Negeri 1 Kahu, employed a quantitative approach to evaluate the impact of Local Genius Mabbelle-based educational media, enhanced with Augmented Reality (Mabbelle-AR), on students' metacognitive skills. The research design included three groups for testing, a limited trial group, a broader trial group, and an experimental group. The assessment of metacognitive skills focused on three core indicators: planning, monitoring, and evaluating. Results indicate that students in the experimental group using Mabbelle-AR demonstrated an 81% improvement in metacognitive skills, while the control group exhibited a 60% increase. These findings highlight Mabbelle-AR efficacy as an educational tool for enhancing students' metacognitive skills, providing an innovative and culturally relevant solution to the persistent challenge of low HOTS levels among Indonesian students. The study suggests that Mabbelle-AR not only promotes critical thinking and problem-solving skills but also supports a culturally grounded approach to integrating technology in education, thereby preparing students with the necessary skills to navigate the complexities of Society 5.0.